Emission and absorption of CO2 during the sea ice formation and melting in the high Arctic - A. P. Nedashkovsky (Лëд и снег)
The carbonate system of the Arctic sea ice is considered. The observations were conducted in the Nansen Basin at the drifting station North Pole-35 in 2007–2008. It was found that total alkalinity – salinity ratio (TA/S) and total inorganic carbon – salinity ratio (TC/S) as well as TA/TC ratio in the ice column and seawater column are similar. The deviations from that pattern were observed in the upper thin layer of the young and first-year ice and in the ice snow cap. The TA/TC ratio (equals to ~2) in the ice snow cap was related with the calcium hydrocarbonate decay and CO₂ removal. It was shown that CO₂ removal was due to its emission into the atmosphere. The CO₂ flux was equal to ~0.02 mol/m² for season. The water formed during melting of the first-year ice was significantly under saturated of CO₂ and hence it may be a sink of 0.05 0.07 mol/m² of the atmospheric CO₂ per season.